The effect of fermented coconut waste to the growth of catfish (ClariasSp) - Farizaldi, Novirman Jamarun, Jafrinur, Yeti Marlida (International Journal of Agricultural Sciences, 2017)
This study aimed to determine the effect of fermented coconut waste on the growth of catfish (Clariassp). The study design used was completely randomized design (CRD) with 4 treatments and 5 replications. Treatments included P0 (0% of fermented coconut waste in the feed), P1 (10% of fermented coconut waste in the feed), P2 (20% of fermented coconut waste in feed), and P3 (30% of fermented coconut waste in the feed). The observed variables were feed consumption, absolute body weight, feed conversion and survival rate. The results showed that using fermented coconut waste for catfish diet significantly (P <0.05) affected feed intake, absolute body weight, feed conversion and live survival of the fish. The conclusion of this research was using 20% of fermented coconut waste in the diet can increase the growth of catfish (Clariassp).